Alveolar capillary dysplasia with misalignment of the pulmonary veins: clinical, histological, and genetic aspects. (August 2018) - Slot, Evelien; Edel, Gabriëla; Cutz, Ernest; van Heijst, Arno; Post, Martin; Schnater, Marco; Wijnen, René; Tibboel, Dick; Rottier, Robbert; de Klein, Annelies
Alveolar capillary dysplasia with misalignment of the pulmonary veins (ACD/MPV) is a rare and lethal disorder mainly involving the vascular development of the lungs. Since its first description, significant achievements in research have led to a better understanding of the underlying molecular mechanism of ACD/MPV and genetic studies have identified associations with genomic alterations in the locus of the transcription factor FOXF1 . This in turn has increased the awareness among clinicians resulting in over 200 cases reported so far, including genotyping of patients in most recent reports. Collectively, this promoted a better stratification of the patient group, leading to new perspectives in research on the pathogenesis. Here, we provide an overview of the clinical aspects of ACD/MPV, including guidance for clinicians, and review the ongoing research into the complex molecular mechanism causing this severe lung disorder.